Babao Dan Reverses Multiple-Drug Resistance in Gastric Cancer Cells via Triggering Apoptosis and Autophagy and Inhibiting PI3K/AKT/mTOR Signaling. (9th July 2021) - Zhao, Jinyan; Lan, Weilan; Peng, Jun; Guan, Bin; Liu, Jie; Zhang, Min; Zhan, Zhixue; Lin, Jiumao
Abstract : Multidrug resistance (MDR) is a critical reason for cancer chemotherapy failure. Babaodan (BBD) is a famous traditional Chinese patent medicine reported to have antigastric cancer activity. However, the roles and molecular mechanisms of the reversal of MDR of gastric cancer by BBD have not been well described until now. Therefore, the purpose of this study was to elucidate further the role of BBD in reversing the MDR of gastric cancer cells and its specific regulatory mechanism via in vitro experiments. To verify our results, MTT, Doxorubicin (DOX) staining, Rhodamin123 (Rho123) staining, DAPI staining, Annexin V-FITC, propidium iodide (PI), Cyto-ID, and western blot assays were performed. To determine whether BBD triggers apoptosis and autophagy through the PI3K/AKT/mTOR signaling, we also applied 3-methyladenine (3-MA), chloroquine (CQ), and 740Y-P (an activator of PI3K). The results showed that BBD reversed the MDR and induced apoptosis and autophagy of SGC7901/DDP cells. Pathway analyses suggested BBD inhibits PI3K/AKT/mTOR pathway activity and subsequent apoptosis-autophagy induction. Inhibition of autophagy with 3-MA and chloroquine (CQ) was performed to confirm that BBD promoted autophagy. PI3K agonist, 740Y-P, further verified BBD inhibition of PI3K/AKT/mTOR pathway activation. In conclusion, BBD may reverse the MDR of gastric cancer cells, induce apoptosis, and promote autophagy via inactivation of the PI3K/AKT/mTOR signaling pathway.